Phosphonium plastic crystal salt alloyed with a sodium salt as a solid-state electrolyte for sodium devices: phase behaviour and electrochemical performance. Issue 12 (16th February 2017) - Makhlooghiazad, Faezeh; Howlett, Patrick C.; Wang, Xiaoen; Hilder, Matthias; MacFarlane, Douglas R.; Armand, Michel; Forsyth, Maria
Abstract : Phase behaviour of a new class of solid state electrolyte with different concentration of Na salt is illustrated for the first time. Abstract : Mixtures of triisobutylmethylphosphonium bis(fluorosulfonyl)imide (P1i444 FSI) with different concentrations of NaFSI display composition-dependent phase behaviour with depression of the melting point upon NaFSI addition and suppression of crystallisation in the middle of the phase diagram and a higher-melting-point, NaFSI-rich mixed-phase region at compositions beyond 60 mol% NaFSI. Thermal treatment of the intermediate compositions results in complete crystallisation of the materials. All compositions showed high ionic conductivity (>10 −5 S cm −1 ) at 20 °C, and Na symmetric cells containing high concentration of NaFSI (Na|[Na0.9 (P1i444 )0.1 ]FSI|Na) were cycled efficiently at 50 and 90 °C at 0.05 and 0.1 mA cm −2, respectively. Intermediate composition (Na|[Na0.6 (P1i444 )0.4 ]FSI|Na) cells were cycled at room temperature and 50 °C at 0.25 mA cm −2 with very low and stable cell polarisation (200 mV).